Correlates of stunting among children in Ghana - Darteh, Eugene Kofuor Maafo (BioMed Central, 2014)
BACKGROUND: Stunting, is a linear growth retardation, which results from inadequate intake of food over a long period of time that may be worsened by chronic illness. Over a long period of time, inadequate nutrition or its effects could result in stunting. This paper examines the correlates of stunting among children in Ghana using data from the 2008 Ghana Demographic and Health Survey (GDHS). METHODS: The paper uses data from the children recode file of the 2008 Demographic and Health Survey (DHS), a nationally representative cross sectional survey conducted in Ghana. A total of 2379 children under five years who had valid anthropometric data were used for the study. Data on the stunting of children were collected by measuring the height of all children under six years of age. A measuring board produced by Shorr Productions was used to obtain the height of the children. Children under 2 years of age were measured lying down on the board while those above 2 years were measured standing. In the DHS data, a z-score is given for the child’s height relative to the age. Both bi-variate and multi-variate statistics are used to examine the correlates of stunting. RESULTS: Stunting was common among males than females. Age of child was a significant determinant of stunting with the highest odd of stunting been among children aged 36–47 months. Region was significantly related to stunting. Children from the Eastern Region were more likely to be stunted than children from the Western Region which is the reference group (OR = 1.7 at p < 0.05). Number of children in household was significantly related to stunting. Children in households with 5–8 children were 1.3 times more likely to be stunted compared to those with 1–4 children (p < .05). Mother’s age was a significant predictor of stunting with children whose mothers were aged 35–44 years being more likely to be stunted. CONCLUSION: Culturally appropriate interventions and policies should be put in place to minimise the effects of the distal, proximal and intermediate factors on stunting among under 5 children in Ghana.